2019
DOI: 10.1039/c9sc03917a
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-responsive hydrogels via peroxide-decorated MXene-initiated polymerization

Abstract: Peroxide-decorated Ti3C2Tx plays a role as an initiator for free-radical polymerization and leads to new opportunities for intelligent optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 65 publications
1
62
0
Order By: Relevance
“…Moreover, the material provides strong optical absorption in the near-IR (NIR) region with potential as a photothermal agent for tumor therapy [ 36 , 37 , 38 ]. Considering the photothermal efficiency of the nanomaterial properties of MXene, we focused on the fabrication process [ 39 ] and application of nanocomposite hydrogels possessing Ti 3 C 2 T x MXene [ 40 , 41 ] to exploit the volume shrinkage promoted by light in NIPAm-based hydrogel materials [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the material provides strong optical absorption in the near-IR (NIR) region with potential as a photothermal agent for tumor therapy [ 36 , 37 , 38 ]. Considering the photothermal efficiency of the nanomaterial properties of MXene, we focused on the fabrication process [ 39 ] and application of nanocomposite hydrogels possessing Ti 3 C 2 T x MXene [ 40 , 41 ] to exploit the volume shrinkage promoted by light in NIPAm-based hydrogel materials [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several MXene-polymer NC hydrogels were prepared and exploited in many applications. 13,18,19,[30][31][32][33][34] Typically, the interactions between MXene nanosheets and other polymers in the hydrogel network arise from polymer chain entanglements, ionic interactions, hydrogen and/or covalent bonding. However, the role of MXene nanosheets in the gelation process of the reported MXene-polymer NC hydrogels varies substantially from noninvolvement to initiating the gelation or acting as a crosslinker.…”
Section: Mxene-polymer Nanocomposite Hydrogelsmentioning
confidence: 99%
“…Recently, Tao et al demonstrated the use of MXene nanosheets as an initiator for the polymerization and the gelation of several acrylic monomers to form different MXene-polyacrylate NC hydrogels. 32 The polymerization of a series of monomers including acrylamide, N-isopropylacrylamide (NIPAM), N,N-dimethylacrylamide (DMA), methyl methacrylate (MMA), and hydroxyethyl methacrylate (HEMA), were initiated by peroxide-decorated MXene (p-Ti 3 C 2 T x ) nanosheets. The p-Ti 3 C 2 T x nanosheets were obtained through a sonication-assisted etching process.…”
Section: Mxene-polymer Nanocomposite Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present contribution, we focus on stimuli-responsive chemical hydrogels. Typical stimuli include variations in temperature [11], pH [11], applied stress [12], magnetic and electromagnetic field [13], ionic strength [14], light [15] and the presence of bioactive species [16]. Redox-responsive gels have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%